Status of a child witness involved in the offence of an adult in criminal procedure - Justyna Głębocka (Revista Brasileira de Direito Processual Penal, 2022)
Giving special importance to the rights of the child, international and European instruments set certain standards aimed at strengthening their guarantees. The standards improving the juvenile offender’s status intend to ensure procedures that take account of the child’s welfare and strengthen their procedural position which, otherwise, because of their age and psychophysical development may be more vulnerable than in the case of an adult’s one. They refer directly to a juvenile offender in case of whom legal proceedings are conducted. This paper aims to clarify underlying issues of a specific procedural configuration, where separate proceedings are conducted regarding a juvenile offender, and separate criminal proceedings before a criminal court are run against an accused adult whose act is related to the juvenile’s act. It attempts to answer, in the context of European standards, the question on the most important rights of a juvenile whose punishable act is in a close relation to an act of an adult offender, and who, for this reason, appears in a criminal trial as a witness. This paper takes into account the European Union standards which result from international children’s rights instruments binding across the EU, the child-specific case law of ECtHR as well as the psychological aspects related to the psychophysical development of minors.